An educational model in the subject of handicrafts and its impact on developing artistic taste among students of the Institute of Fine Arts - طاهر, اسوان (Basrah Arts Journal, 2025)
It aims to reveal the design of an educational model in the subject of handicrafts and its effect on developing the artistic taste of female students of the Institute of Fine Arts.To verify the validity of this goal,the researcher set the null hypotheses to measure the effect of the independent variable on the dependent afterward.Conducting the current research required designing a cognitive achievement test to measure and a skill performance evaluation form to measure artistic outputs. The researcher chose the design with two independent samples with pre- and post-tests, as the research sample was divided into two experimental groups subject to the (educational model) and the other learning by one of the traditional methods and the effect is measured after applying the tools designed for this purpose.The research community consists of first-year(107)students, distributed over(3)art departments,represented by the Department (42) the Calligraphy and Ornamentation(32), and the Audio-Visual(33)for the academic year 2023/2024.Arandom sample was selected,(40)who were distributed into two groups, with (20)as an group and (20) as a control group to apply the tools to them. To extract the results,used the statistical package (SPSS) It was found that the size of the effect that appeared according to the value of (t-test) calculated as follows, regarding the artistic taste test,(0.8),while for the skill test reached (0.9).These two indicators are good since the standard for measuring the ranges between (0.6-0.14),which means that was effective in providing with the skills of the handicraft in its cognitive and skill aspects